Add-On Effect of Chinese Herbal Medicine Bath to Phototherapy for Psoriasis Vulgaris: A Systematic Review. (25th July 2013) - Yu, Jason Jingjie; Zhang, Claire Shuiqing; Zhang, Anthony Lin; May, Brian; Xue, Charlie Changli; Lu, Chuanjian
Abstract : Psoriasis vulgaris is the most common form of psoriasis. Phototherapy has been proven effective for psoriasis, but side effects have become a concern. Chinese herbal medicine (CHM) bath combined with phototherapy has been used in clinical settings, but the additional benefit requires evaluation. This review aims to evaluate the additional benefit and safety of adding CHM bath to phototherapy for psoriasis vulgaris. Cochrane library, PubMed, Embase, CNKI, and CQVIP were searched from their inceptions to 6 August 2012. Randomized controlled trials (RCTs) comparing CHM bath plus phototherapy to phototherapy alone for psoriasis vulgaris were included. Data was analyzed using Review Manager 5.1.0. Thirteen RCTs were included in the review, and eight were included in the meta-analysis. Meta-analysis showed higher efficacy of CHM bath plus phototherapy when compared with phototherapy alone in terms of PASI 60 (RR 1.25; 95% CI: 1.18–1.32). Mild adverse events were reported in ten studies, but these could be alleviated by reducing UV dosage or applying emollient. In conclusion, CHM bath appears to be a beneficial and safe adjunctive therapy to phototherapy for psoriasis vulgaris. However, these results should be interpreted with caution due to the low methodological quality of the included studies.